Unexpected shear dependence of pressure-induced γ-crystals in isotactic polypropylene1. Issue 25 (7th July 2015) - Yang, Shu-Gui; Zhang, Zhengchi; Zhang, Liang-Qing; Zhou, Dong; Wang, Yan; Lei, Jun; Li, Liangbin; Li, Zhong-Ming
<x xml:space="preserve">Abstract</x> Flow and pressure frequently coexist in practical polymer processing operations, but their combined influence on the microstructure of polymer parts has received very limited attention in the academic community.